Fiction readership of U.P. Institute of Library and Information Science students - Parman, Reyna M.; Obille, Kathleen Lourdes B. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2006)
The study investigated the status of UPILIS students. It determined the frequency and recency of reading, purposes in reading, average number of fiction books read in a month, reasons for not reading, fiction preference (in terms of form, genre, language), source of fiction materials, site of reading, and means of selection.
It generated positive results as majority of the respondents occasionally read fiction (30.41 percent) and at the time of study, most had very recent reading. However, a significant proportion of the sample (28.65 percent) was composed of seldom readers and the top reason for this was lack of time. Watching movies turned out to be the most favored activity of non-readers and seldom readers. The big proportion of seldom readers can be attributed to the fact that seniors dominate the sample population who are understandably too busy with so many things.
Though most students read fiction for pleasure, it seems that one important motivating factor in reading fiction is to improve oneself based on the high percentages acquired by school purposes, improving vocabulary, and gaining more information on a specific topic. At large, the fiction readership of the students stands fairly well. The high percentages acquired by ownership, libraries and other people as sources of materials prove that a significant part of the population have healthy readership if those sources are often used. Although friends emerged as the top source of fiction and the ones mostly consulted, it is a positive point that the ILIS Library stands fairly well as source of fiction to those who borrow from libraries, if not the most conducive place for reading. However, it seems that their preference was not that varied, at worst very limited. Most were strongly inclined to novels, to popular genres, and to foreign works.
The ILIS Library was suggested to add more popular novels with genres that the students prefer as well as the not-so-popular novels not-so-popular ones such as short stories and other forms. It was also recommended the provision of more local works to give variety to their choices. In addition, the study saw the need for the improvement of its ventilation, since it was the main complaint of the students, and more effective promotion of its collection. The teachers were suggested to include more popular fiction titles in their required reading lists, with greater emphasis on less favored form and local works to encourage wider readership.
Researchers interested in the readership of its particular group were advised to extend the scope of the study by including the library science students of other schools so as to get larger population and achieve more concluding results on the socio-demographic factors that may have influence on them. A separate study focusing on the influence of other communication medium on reading preference is needed to explain the popularity of novels with film adaptations. It is also interesting to probe deeper on the poor preference on local fiction works.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines. Institute of Library and Information Science -- Students; Readership surveys -- Philippines -- Quezon City; College students -- Books and reading